2017
DOI: 10.1016/j.dcn.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A biomarker of anxiety in children and adolescents: A review focusing on the error-related negativity (ERN) and anxiety across development

Abstract: Overall, 22 studies were included in the current review. A number of patterns emerged, including: 1.) The ERN is enhanced in clinically anxious children at all ages (6-18 years old), regardless of the task used to measure the ERN. 2.) Studies focusing on anxiety symptoms and temperamental fear suggest that the relationship between the ERN and normative anxiety may change across development. 3.) The ERN can predict the onset of anxiety disorders across different developmental periods. 4.) The ERN relates to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
106
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 98 publications
8
106
0
1
Order By: Relevance
“…This is consistent with previous work suggesting that a regression-based approach may be superior to a subtraction-based approach in creating difference scores between conditions (Meyer et al, 2017). Future studies should utilize regression-based, as well as subtraction-based approaches, to further explore this possibility.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous work suggesting that a regression-based approach may be superior to a subtraction-based approach in creating difference scores between conditions (Meyer et al, 2017). Future studies should utilize regression-based, as well as subtraction-based approaches, to further explore this possibility.…”
Section: Discussionsupporting
confidence: 92%
“…While a substantial amount of research has found the ERN to be increased in anxious individuals (Cavanagh & Shackman, 2014; Meyer, 2016; Alexandria Meyer, 2017), few studies have examined the specific anxious phenotype that the ERN indexes. Results from the current study suggest that social anxiety symptoms had the most robust relationship with the ERN in a sample of females during a core risk period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding builds on prior work linking puberty stage with an enhanced ERN (Gorday & Meyer, 2018), demonstrating that pubertal timing may provide another layer of specificity into how developmental changes impact the ERN. Our results also replicate prior work (for a review see;(Meyer, 2017)), that controlling for depressive symptoms, child and adolescent anxiety disorders are marked by an increased ERN. Depressive symptoms attenuated these effects, both amongst early developing and anxious youth, such that increasing depressive symptoms were associated with a reduced ERN (Weinberg, Meyer, et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…An enhanced ERN is robustly associated with anxiety disorders in adults (Cavanagh & Shackman, 2015; Moser et al, 2013), and increasingly among youth (Meyer, 2017). Consequently, the question of when and how this neural sensitivity develops becomes important to understand in what way this biomarker of anxiety differs across typical development.…”
Section: Discussionmentioning
confidence: 99%